2021
DOI: 10.1016/j.ejim.2021.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from pathophysiology: Use of individualized combination treatments with immune interventional agents to tackle severe respiratory failure in patients with COVID-19

Abstract: Aims: Infection by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) may lead to the development of severe respiratory failure. In hospitalized-patients, prompt interruption of the virus-driven inflammatory process by using combination treatments seems theoretically of outmost importance. Our aim was to investigate the hypothesis of multifaceted management of these patients. Methods: A treatment algorithm based on ferritin was applied in 311 patients (67.2% males; median age 63-years; mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…A recent paper reported that elevated plasma levels of IL-6, IL-10 and IP-10 anticipated clinical progression of COVID-19 patients 28 . Our results are in line with the positive treatment outcomes with IL-6 receptor antagonists and with anakinra (the recombinant non-glycosylated form of IL-1ra) because they have showed the need to attenuate the exaggerated IL-6 responses and to enhance the weakened IL-1ra responses 29 . Tocilizumab and sarilumab were shown to decrease the number of days under organ dysfunction and 28-day mortality in the platform adaptive trials REMAP-CAP 30 and RECOVERY 31, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…A recent paper reported that elevated plasma levels of IL-6, IL-10 and IP-10 anticipated clinical progression of COVID-19 patients 28 . Our results are in line with the positive treatment outcomes with IL-6 receptor antagonists and with anakinra (the recombinant non-glycosylated form of IL-1ra) because they have showed the need to attenuate the exaggerated IL-6 responses and to enhance the weakened IL-1ra responses 29 . Tocilizumab and sarilumab were shown to decrease the number of days under organ dysfunction and 28-day mortality in the platform adaptive trials REMAP-CAP 30 and RECOVERY 31, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Not only the included studies, but also other non-RCTs studies came to different results regarding the benefit of IL-6 inhibitors in COVID-19 patients. In a prospective open-label observational study from our department, the use of IL-1 and IL-6 inhibitors showed a reduction in both intubation and mortality rates [28] . On the other hand, there are many observational studies, whose results did not reveal any clinical improvement by using IL-6 inhibitors in COVID-19 patients [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 90%
“…(www.clinicaltrials.gov, NCT04680949) [27] . Similarly, another non-randomized study, where ferritin was used as a biomarker to guide therapy, showed significantly improved clinical outcomes, including reduced mortality rates and progression to severe COVID-19 by early administration of therapy either with anakinra alone or in combination with steroids [30] .…”
Section: Discussionmentioning
confidence: 99%